2013
DOI: 10.4014/jmb.1303.03094
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Cytomegalovirus UL97 D605E Mutation in Korean Stem Cell Transplantation Recipients and Donors

Abstract: Ganciclovir resistance of human cytomegalovirus is associated with mutations in the viral UL97 gene and poses severe problems for immunocompromised patients. In this study, PCRbased restriction fragment length polymorphism and sequencing analyses detected the UL97 D605E mutation in all five clinical isolates from patients with ganciclovir-resistant human cytomegalovirus infection during prolonged ganciclovir therapy, whereas the M460V mutation was only present in 1 of 5 isolates. On the other hand, the detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Zhou be considered as a natural sequence variant. The prevalence of the D605E mutation was 91.8 %, 100 %, and 89.2 %, respectively, in recipients from Japan, Korea, and Taiwan and is therefore considered an important molecular marker of HCMV strains circulating in East Asian countries (2,(22)(23)(24). Some authors suggested that the D605E mutation could partially or fully compensate for the effects of the GCV resistance, conferred by M460V or A594P (25).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou be considered as a natural sequence variant. The prevalence of the D605E mutation was 91.8 %, 100 %, and 89.2 %, respectively, in recipients from Japan, Korea, and Taiwan and is therefore considered an important molecular marker of HCMV strains circulating in East Asian countries (2,(22)(23)(24). Some authors suggested that the D605E mutation could partially or fully compensate for the effects of the GCV resistance, conferred by M460V or A594P (25).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with HIV and AIDS, due to immune deficiency, the antibody against CMV is low or no detectable, therefore, it is necessary to use molecular methods such as PCR to detect and identify CMV-infected patients. Also, Due to several mutations in the main genes of the CMV virus, progression patients with HIV, can be facilitates to diseases such as retinitis, encephalitis and ultimately death [31][32][33].…”
mentioning
confidence: 99%